Integrating Gastrointestinal and Dental Management in Analgesic-Associated Dyspepsia - Festy Ladyani; Indramayanti Warganegara; Ida Fitriyani; Wiwin Wildaniatul Janah; Yogi Dwi Praja Saputra; Yuli Tri Purnamasari; Zada Damar Pasa; Miftha Nazsiroh (Biomedical Research and Theory Letters, 2025)
Dyspepsia is a prevalent gastrointestinal disorder that manifests as epigastric pain, nausea, bloating, postprandial discomfort, and burning sensations in the upper abdomen, often triggered by irregular eating patterns, stress, or the consumption of irritant foods and beverages such as coffee, spicy meals, and fatty products, but it can also be induced by prolonged use of non‑steroidal anti‑inflammatory drugs (NSAIDs). In Indonesia, self‑medication with analgesics remains widespread, yet its impact on dyspepsia in primary care settings is rarely documented, making this study relevant to highlight the clinical features and therapeutic management of drug‑induced dyspepsia. A 39‑year‑old woman presented to Way Halim II Primary Health Center in Bandar Lampung with persistent nausea, vomiting, epigastric pain, bloating, and retrosternal burning after consuming sodium diclofenac daily for three months to relieve untreated dental pain, combined with frequent coffee intake. Endoscopic and laboratory findings were normal, while dental radiography revealed an impacted molar, indicating the underlying source of chronic analgesic use. Clinical data were obtained through anamnesis, physical examination, laboratory evaluation, and imaging, and management consisted of proton pump inhibitor therapy (omeprazole 20 mg), prokinetic agents (domperidone 10 mg), and lifestyle modification, including avoidance of dietary triggers. The patient was advised to undergo dental extraction to eliminate the primary cause of analgesic dependence but declined due to procedural anxiety. Following therapy, symptoms improved significantly, with reduced nausea and epigastric discomfort, demonstrating the effectiveness of pharmacological intervention combined with behavioral modification. This study emphasizes the novelty of identifying dyspepsia linked to prolonged unsupervised NSAID use in a primary care context, underscoring the importance of early recognition of drug‑induced gastrointestinal disorders, patient education on the risks of self‑medication, and multidisciplinary management that integrates gastrointestinal and dental care. Such an approach is critical to prevent recurrence, improve patient outcomes, and strengthen primary health care responses to common but neglected conditions in resource‑limited settings.